Satisfy customers while speeding R&D and staying profitable - Curtis, Carey C; Ellis, Lynn W (Research-technology Management, 1998)
Studies of innovation management effectiveness pinpoint specific practices that will allow companies to increase customer satisfaction and pursue a strategy of speedy R&D-without compromising profitability. The two practices that accomplish this end, when used moderately (although not universally), are Quality Function Deployment for project selection and Stage-Gate Tracking for controlling development. Companies that use Internal Rate of Return as a criterion for project selection have also been found to be move profitable.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-185-376-174-974 tex.type: [object Object]
Keywords: Customer satisfaction; Industrial economics; Profitability; Quality function deployment; Research and development management; Strategic planning; dept.acc